Criteria for performing a strategic environmental assessment of the measures proposed in the land management documentation - Dorosh, O.; Derkulskyi, R.; Dorosh, A. (Land Management, Cadastre and Land Monitoring, 2022)
The article emphasizes that according to the provisions of the Association Agreement between Ukraine and the European Union, the legislation of Ukraine is gradually approaching the law and policy of the EU in the field of environmental protection, since Ukraine has undertaken to implement the provisions of Directive 2001/42/EC of the European Parliament and of the Council dated 27.06.2001 on environmental impact assessment of individual projects and programs.Attention is drawn to the fact that the definition of criteria for assessing the consequences of the implementation of project solutions of land management documentation for the environment, including the possible negative impact on human health, in the process of strategic environmental assessment should take into account the purpose of land management in terms of land protection, the creation of ecologically sustainable agricultural landscapes, forecasting , planning and organization of the rational use and protection of land at the appropriate levels of land management, development and implementation of a system of land management measures to preserve natural landscapes, restore and increase soil fertility, reclamation of disturbed lands and reclamation of unproductive lands, protection of lands from erosion, flooding, drying, landslides , secondary salinization, acidification, waterlogging, compaction, pollution with industrial waste and chemical substances, etc., conservation of degraded and unproductive lands, prevention of other negative phenomena.The author's version of the criteria for the implementation of the strategic ecological assessment of the measures proposed in the land management schemes and technical and economic justifications for the use and protection of the lands of administrative-territorial units, the territories of territorial communities, as well as comprehensive plans for the spatial development of the territories of territorial communities, general plans of settlements, detailed plans of territories, which are at the same time land management and urban planning documentation. The above criteria take into account the peculiarities of the development of land management documentation, which regulates the use and protection of state, communal and private lands, as well as the survey and exploration of lands.Key words: strategic environmental assessment, land management, criteria, land management documentation.
Keywords: strategic environmental assessment; land management; criteria; land management documentation